POTENSI ISI RUMEN SAPI ASAL RUMAH POTONG HEWAN SEBAGAI PAKAN TERNAK RUMINANSIA DI KABUATEN MANOKWARI - Yohosua Kocu; Bambang Tj. Hariadi; Sientje D. Rumetor (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2018)
The aim of this resarch is to determine the potential of rumen content of cattle from slaughterhouse as ruminants feed in Manokwari District, judging from quantity (fresh and dry weight), Quality (DM and OM content), and physical characteristics. Data of research analyzed by tabulation and T-Test. The results showed that each cow that is cut produces an average rumen content of 8.507, 88 g fresh weight or 1.127,16 g dry weight with DM content 89,14% and OM content 89,83%. The average daily cattle slaughter of 5 tails, so that the contents of the rumen generated as much as 10.595,8 g (10,596 kg) fresh weight or 5.635,8 g (5,636 kg) dry weight with 5,024 kg DM and 4,513 kg OM availability. Characteristics of the rumen content after drying is yellowishbrown , texture varies smooth to coarse and aromatic typical of rumen or dried grass.